OP0225 Do worsening scleroderma capillaroscopic patterns predict novel future severe organ involvement in systemic sclerosis? A pilot study. (23rd January 2014) - Smith, V.; Decuman, S.; Sulli, A.; Riccieri, V.; Bonroy, C.; Piette, Y.; Deschepper, E.; De Keyser, F.; Cutolo, M.
Abstract : Background: The clinical expression and course of systemic sclerosis (SSc) may be coupled with serious morbidity and mortality. Effort is being put into the investigation of possible biomarkers. Capillaroscopy is a candidate possible biomarker. Objectives: Assessment of associations of nailfold videocapillaroscopy (NVC) scleroderma patterns ("early", "active" and "late") with novel future severe clinical involvement in a SSc population. Methods: Sixty-six consecutive patients with SSc according to the LeRoy and Medsger criteria underwent nailfold videocapillaroscopic (NVC) assessment at baseline. Videocapillaroscopic images were classified into "normal", "early", "active" or "late" NVC pattern. Clinical evaluation was performed for 9 organ systems (general, peripheral vascular, skin, joint, muscle, gastrointestinal tract, lung, heart and kidney) according to the disease severity scale of Medsger (DSS) at baseline and in the future (18-24 months of follow-up). Severe clinical involvement was defined as category 2-4 per organ of the DSS. Logistic regression analysis with a continuous NVC predictor variable was performed. Results: At the future visit 25/55 patients had novel severe organ involvement in any of the nine organ systems. The number of patients with novel future severe organ involvement rises according to worsening NVC pattern. In this way 0/7 (=0%) of the patients with a "normal" pattern at baseline has a new future severe organ involvement, 2/5 (=40%) of the patients with an "early" pattern at baseline, 10/20 (=50%) of the patients with an "active" pattern at baseline and 13/23 (=57%) of the patients with a "late" NVC scleroderma pattern. In simple logistic regression analysis, the estimated odds ratio, namely 2.16 (95% CI 1.19-4.47, p=0.010), to develop novel future severe organ involvement was stronger according to worsening NVC patterns. In this way the odds ratio for novel future severe organ involvement was 2.16 for the "early", 4.68 for the "active" and 10.14 for the "late" NVC scleroderma pattern versus the "normal" pattern. In a multiple logistic regression analysis, adjusting for disease duration, Leroy subset, and vaso-active medication, the odds ratio, namely: 2.99 (95% CI 1.31–8.82, p=0.007) to develop novel future severe organ involvement was also stronger according to worsening NVC patterns. In this way the odds ratio for new future severe organ involvement was 2.99 for the "early", 8.93 for the "active" and 26.69 for the "late" NVC scleroderma pattern versus the "normal" pattern. Conclusions: This pilot study is the first demonstrating an association between baseline NVC patterns and novel future severe, clinical involvement with stronger odds according to worsening scleroderma patterns. This may indicate a putative role of capillaroscopy as a biomarker and warrants further investigation with large prospective trials. Disclosure of Interest: None Declared